A Conceptual Model of Analogue Gamification to Enhance Learners' Motivation and Attitude - Mee Mee, Rita Wong; Pek, Lim Seong; Von, Wong Yee; Abd Ghani, Khatipah; Tengku Shahdan, Tengku Shahrom; Ismail, Md Rosli; Rao, Yugeshineey Subba (International Journal of Language Education, 2021)
The concept of gamification has spread widely in recent years supported by the development of technology, especially due to the plethora of computers and video games and game apps for other devices. Gamification is the use of game thinking and game mechanics in non-game contexts that support play to engage users in solving problems or created for teaching and learning purposes. Gamification does not mean creating games but making education more engaging and fun with play for learners, without undermining its credibility. In modern education, lessons delivery is associated with the lack of engagement and motivation of learners to participate actively in the learning process. Teachers are increasingly faced with the problem of how to integrate technology and to impart good language learning habits at the level of primary school in Malaysia. Hence, the aim of this study is to propose a conceptual model of analogue gamification to enhance primary school learners’ motivation and attitude.